Synthesis of tricyclic benzimidazole-iminosugars as potential glycosidase inhibitors via a Mitsunobu reaction. (1st November 2019) - Yan, Lianhai; Lui, Hui; Sun, Jiajing; Gao, Ligang; Lu, Xin; Li, Xiaoliu; Chen, Hua
Abstract: A series of tricyclic benzimidazole-iminosugars 1(a –f) and 2(a –f) were synthesized and evaluated for their their inhibitory activities against five glycosidases. The synthesis initiated from the benzyl protected sugar (aldehyde) 5 that reacted with 1, 2-diaminobenzene to afford aldo-benzimidazole 6 by the iodine-induced oxidative condensation. Then, tricyclic compound 7 was obtained in high yields of 73%–87% by the key Mitsunobu reaction through intramolecular cyclization of the unprotected OH and the NH in 6 . After removal of the benzyl group in CF3 SO3 H, the target tricyclic benzimidazole-iminosugars 1 and 2 were achieved. The protocol was effective for the preparation of the tricyclic iminosugar in satisfactory yield. The results of the glycosidase inhibitory activities of 1 and 2 showed that three compounds derived from d -ribose exhibited specific and good inhibitory effects on β-glucosidase. Among them, 1e-1 was the best one with IC50 value of 5.37 μM. All hydroxyl groups on β-position would be favourable to the inhibitory activity of such tricyclic benzimidazole-iminosugars against β-glucosidase. Graphical abstract: A series of tricyclic benzimidazole-iminosugars 1(a –f) and 2(a –f) were constructed through the intramolecular cyclization of NH and OH by the key Mitsunubo reaction, providing an effective protocol for the preparation of the tricyclic iminosugars. Three compounds derived from d -ribose exhibited specific and good inhibitory effects on β-glucosidase. Image 1 Highlights: Tricyclic benzimidazole-iminosugars 1(a –f) and 2(a –f) were synthesized by a Mitsunobu reaction. Such tricyclic benzimidazole-iminosugars had the sp 2 -character on their anomeric carbons. Tricyclic benzimidazole-iminosugars derived from d -ribose exhibited specific and good inhibitory effects on β-glucosidase. The configurations of hydroxyl groups might play a very important role on their anti-glycosidase activity.